A protocol to transfer a fed‐batch platform process into semi‐perfusion mode: The benefit of automated small‐scale bioreactors compared to shake flasks as scale‐down model. (19th December 2018) - Janoschek, Sabrina; Schulze, Markus; Zijlstra, Gerben; Greller, Gerhard; Matuszczyk, Jens
Abstract : Continuous processes such as perfusion processes can offer advantages compared to fed‐batch or batch processes in bio‐processing: improved product quality (e.g. for labile products), increased product yield, and cost savings. In this work, a semi‐perfusion process was established in shake flasks and transferred to an automated small‐scale bioreactor by daily media exchange via centrifugation based on an existing fed‐batch process platform. At first the development of a suitable medium and feed composition, the glucose concentration required by the cells and the cell‐specific perfusion rate were investigated in shake flasks as the conventional scale‐down system. This lead to an optimized process with a threefold higher titer of 10 g/L monoclonal antibody compared to the standard fed‐batch. To proof the suitability and benefit as a small‐scale model, the established semi‐perfusion process was transferred to an automated small‐scale bioreactor with improved pH and dissolved oxygen control. The average specific productivity improved from 24.16 pg/(c*d) in the fed‐batch process and 36.04 pg/c*d in the semi‐perfusion shake flask to 38.88 pg/(c*d) in the semi‐perfusion process performed in the controlled small‐scale bioreactor, thus illustrating the benefits resulting from the applied semi‐perfusion approach, especially in combination with controlled DO and pH settings. © 2019 The Authors. Biotechnology Progress published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2757, 2019.